Competition Policy in Small Distant Open Economies: Some Lessons from the Economics Literature - Lewis Evans; Patrick Hughes (New Zealand Government, The Treasury, 2003)
New Zealand is a small open economy that is remote from all major markets. The smallness and remoteness of New Zealand combine to imply that this country has, at least quantitatively, distinctive features for the regulation of economic activity by competition law. The isolation and small size of the economy mean that typically all but exporting firms are small as judged on a world scale, and that domestic markets are small and generally highly concentrated. This paper reviews the economic literature on the implications of an economy's size and isolation for competition law. The literature suggests that principles underlying competition law do not change for small economies, but that the application of competition law should be different. In small economies, low regulatory and tax barriers to trade dominate the importance of competition law for good economic performance of domestic markets. In these economies, competition law should focus on economic benefit/detriment evaluations of mergers and trade practices rather than rules of thumb of the sort based on measures of market structure and indicators of competition, or those aimed at prohibiting particular practices per se. Producers' surplus should not be de-emphasised in the calculation of benefits and detriments in small economies; particularly for activities that relate in any way to (potential) export activity. For any economy, particularly in the presence of competition, cooperation enhances economic performance in specific circumstances. In small economies cooperation can be particularly efficient-for example, in achieving scale and thereby export performance-although it may entail interaction among a large fraction of players in an industry. The approach that the literature suggests to the application of competition law in small economies places relatively heavy weight on dynamic efficiency as the criterion for competition law design and enforcement. It is squarely in accord with recommendations in the literature on desirable competition law for the so-called new economy.
Keywords: K21; L40; L50; 330; Small; Isolated; Economy; Antitrust; New Zealand; Producer Surplus: Consumer Surplus; Competition Law; Economic Benefit; Economic Detriment; Rule of Reason